Acid‐Triggered Dual‐Functional Hydrogel Platform for Enhanced Bone Regeneration - Yao Xiao; Jinjin Ma; Xiaonan Yuan; Huan Wang; Fengyu Ma; Jun Wu; Qianglong Chen; Jie Hu; Lijie Wang; Zhendong Zhang; Chao Wang; Jiaying Li; et al. (Advanced Science)
Abstract Stem cell implantation holds promise for enhancing bone repair, but risks of pathogen transmission and malignant cell transformation should not be ignored. Compared to stem cell implantation, recruitment of endogenous stem cells to injured sites is more critical for in situ bone regeneration. In this study, based on the acidic microenvironment of bone injury, an HG‐AA1:1‐SDF‐1α composite hydrogel with a dual‐control intelligent switch function is developed by incorporating stromal cell‐derived factor (SDF‐1α), arginine carbon dots (Arg‐CDs), and calcium ions (Ca2+) into the oxidized hyaluronic acid/gelatin methacryloyl (HG) hydrogel. The acidic microenvironment triggers the first switch (Schiff base bond is broken between HG‐AA1:1 and SDF‐1α) of HG‐AA1:1‐SDF‐1α composite hydrogel to continuously release SDF‐1α. Compared to the neutral (pH 7.4) media, the cumulative release of SDF‐1α in acidic (pH 5.5) media is ≈2.5 times higher, which enhances the migration and recruitment of endogenous mesenchymal stem cells (MSCs). The recruited MSCs immediately initiate the second switch and metabolize Arg‐CDs into the bioactive nitric oxide (NO) in the presence of Ca2+, activating NO/cyclic guanosine monophosphate (cGMP) signaling pathway to promote angiogenesis. Therefore, the engineered HG‐AA1:1‐SDF‐1α composite hydrogel shows promising potential to achieve “coupling osteogenesis and angiogenesis” for bone regeneration.